Impact of low health literacy on patients’ health outcomes: a multicenter cohort study - Shahid, Rabia; Shoker, Muhammad; Chu, Luan Manh; Frehlick, Ryan; Ward, Heather; Pahwa, Punam (BMC health services research, 2022)
Background This study aims to assess the health literacy of medical patients admitted to hospitals and examine its correlation with patients’ emergency department visits, hospital readmissions, and durations of hospital stay. Methods This prospective cohort study recruited patients admitted to the general internal medicine units at the two urban tertiary care hospitals. Health literacy was measured using the full-length Test of Functional Health Literacy in Adults. Logistic regression analyses were performed to examine the correlation between health literacy and the desired outcomes. The primary outcome of interest of this study was to determine the correlation between health literacy and emergency department revisit within 90 days of discharge. The secondary outcomes of interest were to assess the correlation between health literacy and length of stay and hospital readmission within 90 days of discharge. Results We found that 50% had adequate health literacy, 32% had inadequate, and 18% of patients had marginal health literacy. Patients with inadequate health literacy were more likely to revisit the emergency department as compared to patients with adequate health literacy (odds ratio: 3.0; 95% Confidence Interval: 1.3–6.9, p = 0.01). In patients with inadequate health literacy, the mean predicted probability of emergency department revisits was 0.22 ± 0.11 if their education level was some high school or less and 0.57 ± 0.18 if they had completed college. No significant correlation was noted between health literacy and duration of hospital stay or readmission. Conclusions Only half of the patients admitted to the general internal medicine unit had adequate health literacy. Patients with low health literacy, but high education, had a higher probability of emergency department revisits.